Synthesis and evaluation of antitumor activity of new 4-substituted thieno[3,2-d]pyrimidine and thienotriazolopyrimidine derivatives - Hafez Hend N.; El-Gazzar Abdel-Rhman B. A. (Acta Pharmaceutica)
3-Methyl-6-phenyl-2-thioxo-2,3-dihydrothieno[3,2-d]pyrimidin- 4(1H)-one (2), on treatment with phosphorous oxychoride, affored 4-chloro-3-methyl-6-phenyl -thieno[3,2-d]pyrimidine- 2(3H)-thione (3). A series of novel 6-phenyl-thieno[3,2-d]pyrimidine derivatives 4-9 bearing different functional groups were synthesized via treatment of compound 3 with different reagents. On the other hand, compound 2 was used to synthesize ethyl-[(3-methyl-6-phenyl-2-thioxo-2,3-dihydrothieno[ 3,2-d]pyrimidin-4-yl)-oxy]acetate (10), 2-hydrazinyl- -3-methyl-6-phenyl-thieno[3,2-d]pyrimidin-4(3H)-one (11), 3-methyl-2-(methyl-sulfanyl)-6-phenyl-thieno[3,2-d]pyrimidin- 4(3H)-one (12) and N-(phenyl)/4-chlorophenyl or methoxy- phenyl)-2-[(3-methyl-4-oxo-6-phenyl-3,4-dihydrothieno[ 3,2-d]pyrimidin-2-yl)-sulfanyl]-acetamide (13a-c). In addition, compound 12 was used to synthesize thieno[1,2,4] triazolopyrimidine derivatives 14 and 15 and 3-methyl-2-(methyl-sulfonyl)-6-phenyl-thieno[3,2-d]pyrimidin-4(3H)-one (16) through the reaction with the respective reagents. Moreover, the reaction of 16 with 4-phenylenediamine gave 2-[(4-aminophenyl)-amino]-3-methyl-6-phenyl-thieno[3,2-d] pyrimidin-4(3H)-one (17), which reacted with methanesulfonyl chloride to afford N-{4-[(3-methyl-4-oxo-6-phenyl-3H,4H- -thieno[3,2-d]pyrimidin-2-yl)-amino]phenyl}-methanesulfonamide (18). The majority of the newly synthesized compounds displayed potent anticancer activity, comparable to that of doxorubicin, on three human cancer cell lines, including the human breast adenocarcinoma cell line (MCF-7), cervical carcinoma cell line (HeLa) and colonic carcinoma cell line (HCT- 116). Compounds 18, 13b and 10 were nearly as active as doxorubicin whereas compounds 6, 7b and 15 exhibited marked growth inhibition, but still lower than doxorubicin.